Analisis Efektivitas Perpindahan Panas Kondensor pada Proses Destilasi Daun Serai Wangi - Karo Karo, Septa Fernando; Darianto, Darianto; Idris, Muhammad (Universitas Medan Area, 2023)
The condenser is one of the main components in a system that condenses vapor into liquid. The performance of a condenser can be influenced by heat transfer rate, vacuum pressure, and effectiveness. The aim of this research is to determine the effectiveness value and variables that affect the performance of the condenser in the lemongrass distillation process, as well as to understand the influence of heat transfer rate on film condensation (condensate vapor mass). The research method used the Log Mean Temperature Difference (LMTD) and Effectiveness - Number of Transfer Unit (NTU) to calculate the effectiveness value and compared the condensate vapor mass with the mass flow rate of vapor to obtain film condensation. The research results showed an effectiveness value of 89% in the condenser, and the condensate vapor mass accounted for 36% of the biooil. The influencing variables were a capacity ratio of 0.0182840, a heat transfer rate of 186544.68 W, and an LMTD of 29.74°C. Therefore, it can be concluded that the condenser used in the lemongrass distillation process still performs well.